Advancing innovation for vaccine manufacturers from developing countries: Prioritization, barriers, opportunities. Issue 8 (22nd February 2021) - Hayman, Benoit; Bowles, Alex; Evans, Beth; Eyermann, Elizabeth; Nepomnyashchiy, Lyudmila; Pagliusi, Sonia
Highlights: 95% of respondents manufacturers have a strategy to pursue innovation. Innovation targeted at low- and middle- income countries. Partnerships with biotechs and universities key in driving innovation. Access to partnerships, in-licensing/ joint ventures seen as barrier to novel vaccines. Abstract: Development of novel vaccines and improving existing vaccines is critical to addressing areas of unmet or under-addressed health needs globally and to improving existing vaccination coverage and equity. However, vaccine innovation is costly and highly complex. To understand how vaccine manufacturers from developing countries approach innovation, a survey was conducted among company members of the Developing Countries Vaccine Manufacturers Network, in collaboration with the Clinton Health Access Initiative. The survey confirmed that vaccine manufacturers from developing countries are committed to vaccine innovation: 95% of respondents have interest in pursuing vaccine innovation, with strategies targeted towards supplying to low- and middle-income countries. Key barriers to innovation were also surveyed, with respondents highlighting challenges regarding access to in-licensing or joint venture partnerships, financing, and regulatory barriers. Opportunities for innovation are also discussed.